2019
DOI: 10.1080/1744666x.2019.1624527
|View full text |Cite
|
Sign up to set email alerts
|

Additive immunosuppressive effect of leflunomide and hydroxychloroquine supports rationale for combination therapy for Sjögren’s syndrome

Abstract: Objective: Effective treatment for primary Sjögren's syndrome (pSS) is not available. pSS immunopathology involves a variety of immune-cells and dysregulated pathways; targeting several pathways instead of only one could therefore be effective. Treatment with leflunomide (LEF) and hydroxychloroquine (HCQ) might be successful given their unique immunosuppressive properties. We aimed to study the in vitro effects of LEF, HCQ and their combination on T-and B-cell proliferation, cytokine and immunoglobulin product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Even tofacitinib, which targets numbers of pro-inflammatory cytokines, was not successful. Leflunomide, a pyrimidine synthesis inhibitor that inhibit B-lymphocyte proliferation and cell cycle progression [10,32], as well as PI3K and BTK inhibitors (targeting at the same time CXCL13, BAFF and IL6 signaling [33]) decreased B-lymphocyte viability in co-cultures. Lastly, PI3K was the only inhibitor to maintain an inhibitory effect under poly(I:C) stimulation, which suggests that in a local IFN-rich environment, such as pSS salivary glands, PI3K inhibition might be the most efficient option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even tofacitinib, which targets numbers of pro-inflammatory cytokines, was not successful. Leflunomide, a pyrimidine synthesis inhibitor that inhibit B-lymphocyte proliferation and cell cycle progression [10,32], as well as PI3K and BTK inhibitors (targeting at the same time CXCL13, BAFF and IL6 signaling [33]) decreased B-lymphocyte viability in co-cultures. Lastly, PI3K was the only inhibitor to maintain an inhibitory effect under poly(I:C) stimulation, which suggests that in a local IFN-rich environment, such as pSS salivary glands, PI3K inhibition might be the most efficient option.…”
Section: Discussionmentioning
confidence: 99%
“…Given some recent clinical results [10], we also looked at the effect of the association of leflunomide and hydroxychloroquine. Leflunomide decreased B-lymphocyte viability in coculture, but this effect was lost in the presence of poly(I:C) ( Figure 5I and J).…”
Section: Interactions Between Sgecs and B Lymphocytes Require Mostly mentioning
confidence: 99%
“…Immunosuppressive treatment, in general, mainly acts on the proliferating cells, such as T and B cells, and stops their differentiation and expansion. Hydroxychloroquine (HCQ) modifies activity of the antigen-presenting cells (DCs and monocytes) (van der Heijden et al, 2019). In the light of given data, HCQ could have the greatest impact on our results.…”
Section: Serum Componentmentioning
confidence: 81%
“…The speci c mechanism may be that after autophagy inhibition in CD4 + T cells, CDKN1B aggregation of a negative regulator of cyclin-dependent kinase is promoted, causing CD4 + T cells to not enter the S phase after T cell receptor (TCR) stimulation and inhibiting CD4 + T cell proliferation [53] . Another study also showed that HCQ inhibits peripheral blood T cell proliferation in patients with pSS by inhibiting TCR/ Toll-like receptor 9 [54] . Interestingly, this study found that CD4 + T cell proliferation was inhibited after RAPA-induced autophagy, contrary to the expected results of enhanced proliferation with increased autophagy levels.…”
Section: Discussionmentioning
confidence: 94%